Foreign Office and predecessors: Political and Other Departments: Supplements to General Correspondence before 1906 (F.O. 97) (Records of the Public Record Office., 1960)
Foreign Office 97 (class "FO 97") "contains correspondence, enclosures, papers relating to various cases and claims, memoranda, etc., supplementary to the general series of correspondence for individual countries. Included are details of court proceedings, treaties, letters and telegrams. This series is arranged in alphabetical order under names of countries and contains a miscellaneous collection of papers"--From online catalog of the Great Britain National Archives.